Problematika al-Qur’an (Telaah Kritis atas Pandangan Sarjana Barat) - Djidin, M (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2011)
This article critically analyses Western scholar’s views of Qur’anic transmission from the earlier era of Prophet Muhammad up to era ofunification of themushaf (Qur’an). Western scholars lie their skepticism to the authenticity of the Qur’an on the pre-assumsion that the Qur’an has been intervented by the Muslim scholar after the death of Muhammad, specially related to the text of Qur’an. So that, by using historical approach, the article displies the historical facts of Qur’anic transmission, and than analyzes how the Western Scholar deal with that facts. After analyzing with critical discourse method, the article concluded that in the time of Qur’anic transmission, there are many opened weakneses which were entered by Western scholar to say that the Qur’an was not genuine revealed from God, but there are any modifications in several pleaces of the versus. Eventhough, that opinion has been weak if arguedvis a viswith reliability and consistency of the text and context of Qur’an since the beginning of it’s collection. Besides, Arabics, as a permanent language of the Qur’an, has a harmonious regularity and a beautiful style comparing with another literature works in the contemporary Islam.